A novel uORF regulates folliculin to promote cell growth and lysosomal biogenesis during cardiac stress - Bencun, Maja; Spreyer, Laura; Boileau, Etienne; Eschenbach, Jessica; Frey, Norbert; Dieterich, Christoph; Völkers, Mirko (Scientific reports, 2025)
Pathological cardiac remodeling is a maladaptive response that leads to changes in the size, structure, and function of the heart. These changes occur due to an acute or chronic stress on the heart and involve a complex interplay of hemodynamic, neurohormonal and molecular factors. As a critical regulator of cell growth, protein synthesis and autophagy mechanistic target of rapamycin complex 1 (mTORC1) is an important mediator of pathological cardiac remodeling. The tumor suppressor folliculin (FLCN) is part of the network regulating non-canonical mTORC1 activity. FLCN activates mTORC1 by functioning as a guanosine triphosphatase activating protein (GAP). Our work has identified a regulatory upstream open reading frame (uORF) localized in the 5′UTR of the FLCN mRNA. These small genetic elements are important regulators of protein expression. They are particularly important for the regulation of stress-responsive protein synthesis. We have studied the relevance of the FLCN uORF in the regulation of FLCN translation. We show that FLCN downregulation through the uORF is linked to cardiomyocyte growth and increased lysosomal activity. In summary, we have identified uORF-mediated control of RNA translation as another layer of regulation in the complex molecular network controlling cardiomyocyte hypertrophy.
Gesehen am 26.08.2025